Impact of titanium dioxide nanoparticles on the nutritional composition of haematococcus pluvialis - Manishaa Sri, Mahendran (2023)
Haematococcus pluvialis (H. pluvialis) is farmed worldwide due to its nutrient-rich properties and provides multiple benefits to human health. However, the wide usage of titanium dioxide nanoparticles (TiO2 NPs) causes nano pollution of water bodies due to the presence of TiO2 NPs residue in domestic and industrial wastes which may affect the nutritional quality of H. pluvialis. Hence, this study aimed to investigate the interaction and accumulation of TiO2 NPs on H. pluvialis and determine the changes in biomass and nutritional value of H. pluvialis due to the exposure to TiO2 NPs. The cellular interaction and accumulation of TiO2 NPs on H. pluvialis were examined through Fourier transformed infrared (FTIR) spectroscopy and Scanning electron microscope (SEM). The loss in biomass together with the macromolecules, pigments, and phenolic compounds of H. pluvialis was investigated upon treating with various concentrations of TiO2 NPs (5, 10, 25, 50 and 100 µg/mL) for 24, 48 72 and 96 h. The Energy dispersive X-ray (EDX) analysis confirmed the surface accumulation of TiO2 NPs on H. pluvialis cells, while SEM images evidenced the surface alterations and damage of the treated cells. The functional groups such as hydroxyl, amine, methyl, amide I, amide II, carboxyl, carbonyl, and phosphate groups from the cell wall of the H. iv pluvialis were identified to be possibly involved in the interaction of TiO2 NPs with H. pluvialis. The results showed that the treatment of H. pluvialis with TiO2 NPs caused a dose and time-dependent reduction in biomass, macronutrients, pigments, and phenolic compounds. The highest detrimental effects were found at 96 h with the reported values of 43.29 ± 2.02%, 67.05 ± 0.99%, 48.67 ± 0.18% and 44.22 ± 0.49% reduction in biomass, proteins, carbohydrates and lipids, respectively, along with 39.31 ± 2.54%, 34.92 ± 0.84%, 34.24 ± 0.36%, and 42.66 ± 0.94% loss in chlorophyll-a, carotenoids, astaxanthin, and total phenolic compounds of H. pluvialis for 100 µg/mL of TiO2 NPs. Hence, the study confirmed that the exposure of TiO2 NPs is detrimental to H. pluvialis where the interaction and accumulation of TiO2 NPs on H. pluvialis caused reduction in biomass, macromolecules, pigments, and total phenolic compounds. The finding on how TiO2 NPs affect nutrient microalga H. pluvialis’s nutritional qualities will be helpful in evaluating the environmental effect of TiO2 NPs in waterways. The data will also aid in the development of methods for screening TiO2 NPs contamination in microalgae which may otherwise pose delirious effects to the consumers